2019
DOI: 10.1002/jobm.201800729
|View full text |Cite
|
Sign up to set email alerts
|

Changes of volatile organic compounds and bioactivity of Alternaria brassicae GL07 in different ages

Abstract: Plant endophytes are rich in secondary metabolites and are widely used in medicine, chemical, food, agriculture, and other fields. Here, an endophytic fungus is isolated from Ginkgo biloba L. leaves and identified as Alternaria brassicae GL07 through genotypic characterizations. It can produce fruity scented volatiles. The analysis of volatile organic compounds (VOCs) was done by gas chromatography–mass spectrometry. A total of 32 components were identified; and at different culture times, the composition of V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…In addition, the experiment with rice as a culture medium suggests that the volatilome evolves with the age of the fungus, which is in accordance with previous studies on other fungal species [10,15,42]. Pan et al [42] analyzed the VOC profile of Alternaria brassicae and reported a reduction in the diversity of VOCs as the fungus aged, which is the same trend we found in Pc, where the 35-day-old culture had less VOC diversity than the 15-day-old culture.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the experiment with rice as a culture medium suggests that the volatilome evolves with the age of the fungus, which is in accordance with previous studies on other fungal species [10,15,42]. Pan et al [42] analyzed the VOC profile of Alternaria brassicae and reported a reduction in the diversity of VOCs as the fungus aged, which is the same trend we found in Pc, where the 35-day-old culture had less VOC diversity than the 15-day-old culture.…”
Section: Discussionsupporting
confidence: 90%
“…Components with mass spectral similarity greater than 80% were considered reliable. The relative content of each substance was calculated by the normalization algorithm [19].…”
Section: Gas Chromatography-mass Spectrometry (Gc-ms) Analysis Of Fun...mentioning
confidence: 99%
“…The non-polar composition of endophytes is poorly understood. Endophytic fungi mainly synthesize ethers, acids, amines, alkenes and benzene [ 58 ]. Fungal strain O. senegalensis NR-03 synthesized different non-polar components depending on the content of the culture medium.…”
Section: Discussionmentioning
confidence: 99%
“…The secondary metabolites produced by the fungal strain in each medium were extracted by ethyl acetate then dissolved in dichloromethane. The non-polar chemical composition of the endophytic fungus O. senegalensis NR-03 was subjected to gas chromatography—mass spectral (GC-MS) analysis, as previously reported [ 37 , 58 ]. The GC-MS system consisted of an Agilent 7890 gas chromatograph coupled to an Agilent 5975 mass detector (Agilent Technologies, New York, USA) and an Agilent 7693 autosampler.…”
Section: Methodsmentioning
confidence: 99%